Cooperative Interaction between Acid and Copper Resistance in Escherichia coli - Kim, Yeeun; Lee, Seohyeon; Park, Kyungah; Yoon, Hyunjin (Journal of Microbiology and Biotechnology, 2022)
The persistence of pathogenic Escherichia coli under acidic conditions poses a serious risk to food safety, especially in acidic foods such as kimchi. To identify the bacterial factors required for acid resistance, transcriptomic analysis was conducted on an acid-resistant enterotoxigenic E. coli strain and the genes with significant changes in their expression under acidic pH were selected as putative resistance factors against acid stress. These genes included those associated with a glutamate-dependent acid resistance (GDAR) system and copper resistance. E. coli strains lacking GadA, GadB, or YbaST, the components of the GDAR system, exhibited significantly attenuated growth and survival under acidic stress conditions. Accordantly, the inhibition of the GDAR system by 3-mercaptopropionic acid and aminooxyacetic acid abolished bacterial adaptation and survival under acidic conditions, indicating the indispensable role of a GDAR system in acid resistance. Intriguingly, the lack of cueR encoding a transcriptional regulator for copper resistance genes markedly impaired bacterial resistance to acid stress as well as copper. Conversely, the absence of YbaST severely compromised bacterial resistance against copper, suggesting an interplay between acid and copper resistance. These results suggest that a GDAR system can be a promising target for developing control measures to prevent E. coli resistance to acid and copper treatments.
Keywords: Acids; Copper; Escherichia coli; Escherichia coli Infections; Escherichia coli Proteins; Gene Expression Regulation, Bacterial; Humans; Hydrogen-Ion Concentration; Sigma Factor; acid resistance; copper resistance; Escherichia coli; foodborne pathogen